Reuse of ultrafine mineral wool production waste in the manufacture of refractory concrete. (1st July 2016) - Stonys, R.; Kuznetsov, D.; Krasnikovs, A.; Škamat, J.; Baltakys, K.; Antonovič, V.; Černašėjus, O.
Abstract: The paper deals with the mineral wool production waste (cupola dust - CD), presents CD characterization and aims to reuse CD in production of refractory concrete with calcium aluminate cement. The study of CD covers its chemical, phase and thermal analyses along with the morphological study and determination of particles size distribution. Zeta-potential, electrical conductivity and pH values of CD suspension are presented in the paper as well. Commercial microsilica additive in refractory concrete has been replaced with cupola dust. Compositions of refractory concrete have been prepared by incorporating 1%, 2% and 3% of CD. The bulk density, ultrasonic wave velocity, cold crushing strength and thermal shock resistance of the created refractory concrete have been determined. Based on experimental results, it has been found that cupola dust may be used for the production of refractory concrete. The environmental impact related to the CD reuse in refractory concrete production has been evaluated as well. Highlights: The characterization of ultrafine waste (cupola dust) of mineral wool production. The reuse of cupola dust in calcium aluminate cement (CAC) refractory concrete. The influence of cupola dust on properties of CAC refractory concrete.